Identification of adenylyl cyclase isoforms mediating parathyroid hormone- and calcitonin-stimulated cyclic AMP accumulation in distal tubule cells - Kittikulsuth, Wararat (BMC Nephrol, 2017)
BACKGROUND: The distal convoluted tubule (DCT) is an important nephron site for parathyroid hormone (PTH) and calcitonin regulation of urinary divalent cation excretion. These hormones exert their effects on the DCT in substantial part through activation of adenylyl cyclase (AC); however, it is unknown which AC isoforms are involved. METHODS: To examine this, two mouse DCT cell lines were studied: 209 and D1 cells. AC isoform mRNA expression was analyzed by real-time PCR. Cyclic AMP was measured using enzyme immunoassay. RESULTS: Calcitonin, but not PTH, stimulated cAMP accumulation in 209 cells, while PTH, but not calcitonin, increased cAMP content in D1 cells. Both cell types expressed AC3, AC4, AC6, AC7, and AC9 mRNA; in both cell types, AC6 mRNA was most abundant, followed by AC9, then AC3 and AC7, with relatively very small amounts of AC4 mRNA. Microdissected mouse DCT had a similar pattern of AC isoform mRNA expression although AC5 mRNA was detected. Individual siRNA knockdown of AC6 and AC9 reduced calcitonin-stimulated cAMP accumulation in 209 cells and PTH-induced cAMP levels in D1 cells. Knockdown of AC3 had no effect on hormonal augmentation of cAMP in either cell line. Surprisingly, knockdown of AC7 increased calcitonin-induced cAMP accumulation in 209 cells as well as PTH-stimulated cAMP content in D1 cells. CONCLUSIONS: Taken together, these findings indicate that AC6 and AC9 mediate calcitonin- and PTH-stimulated cAMP accumulation in DCT cells, while activation of AC7 may paradoxically reduce the stimulatory effects of PTH and calcitonin on cultured DCT cAMP levels.